Efeito modulador da glutationa na liberação de gaba induzida por glutamato em retinas de embrião de galinha - PEREIRA, Tiago de Lima (Universidade Federal do Pará, 2012)
The γ-aminobutyric acid (GABA) and glutamate are, respectively, major inhibitory and excitatory neurotransmitters in the central nervous system (CNS) and are essential to the visual processing. Studies show that glutamate induces the release of GABA in the retina, but the mechanisms involved in this release are not well elucidated. Previous work also showed that thiols compounds regulate GABA release, but are not well defined the effects of compounds containing sulfhydryl (-SH) on endogenous levels of this neurotransmitter in the retina. In this context, glutathione (GSH) besides being the most important thiols compounds, have demonstrated perform a neuromodulatory role in the release of neurotransmitters. Thus, the objective of this study was to evaluate a possible modulatory effect of GSH on the release of GABA mediated by glutamate in the retina of chick embryo. For this study, we used as experimental model, retinal tissue intact chick embryo, with seven or eight days of development. In tests of release of GABA, the retinas were treated with GSH (100 and 500 μM), glutamate (50 and 500 μM) and Buthionine Sulfoximine (BSO), an inhibitor of glutathione synthesis, (50 μM) per 15 minutes, and GABA levels released into the extracellular medium were quantified by High Performance Liquid Chromatography (HPLC). For release experiments of thiols compounds, the retinas were incubated with glutamate 100 μM (with or without Na +) per 15 minutes, and their extracellular levels were determined by reaction with DTNB and quantified by spectrophotometry (412 nm). The results show that glutamate, as well as GSH, release GABA. Our data also show that BSO attenuates the release of GABA promoted by glutamate. Furthermore, we demonstrate that glutamate induces release of thiol compounds regardless of sodium. Therefore, it is known that glutamate is able to release thiols and GABA, among them, GSH is most abundant and responsible for also release GABA. It is also known that once inhibited GSH synthesis by BSO, the release of GABA induced by glutamate is attenuated. Then, it is suggested a possible modulation of GSH in the release of GABA induced by glutamate in retina intact chicken embryo.